High discharge rate electrodeposited zinc electrode for use in alkaline microbattery - Nor Hairin, Assayidatul Laila; Othman, Raihan; Ani, Mohd Hanafi; Saputra, Hens (IIUM Press, International Islamic University Malaysia, 2011)
High discharge rate zinc electrode is prepared using the electrodeposition process. The electrolytic bath consists of zinc chloride as the metal source and ammonium chloride as the supporting electrolyte. The concentration of the supporting electrolyte is varied from zero until 4 M, while the concentration of zinc chloride is fixed at 2 M. The aim is to produce a porous zinc coating with an enhanced and intimate interfacial area per unit volume. These characteristics shall contribute towards reduced ohmic losses, improved active material utilization, and subsequently producing high rate capacity electrochemical cell. Nitrogen physisorption at 77 K is used to measure the BET surface area and pore volume density of the zinc electrodeposits. The electrodeposited zinc electrodes are then fabricated into alkaline zinc-air microbattery measuring 1 cm2 area x ca. 305 μm thick. The use of inorganic MCM-41 membrane separator enables the fabrication of a compact cell design. The quality of the electrodeposited zinc electrodes is gauged directly from the electrochemical performance of zinc-air cell. Zinc electrodeposits prepared from electrolytic bath of 2 M NH4Cl produces the highest discharge capacity.